Business Unit Opinions on Printing VAT invoices Using the APTax rogram in Luang Prabang Province - Phommalath, Somphavanh; YANGSANSAY, Chahue; SOULIYASACK, Somkhit (Souphanouvong University Journal Multidisciplinary Research and Development, 2025)
This research aims to examine the opinions of business units in Luang Prabang Province regarding the use of the APTax program for printing Value Added Tax (VAT) invoices. A quantitative research method was employed, utilizing a structured questionnaire distributed via Google Forms to businesses that use the APTax program. A total of 239 responses were collected. The data were analyzed using SPSS statistical software, applying descriptive statistics such as frequency, percentage, mean, and standard deviation. The demographic analysis revealed that 53.1% of respondents were female and 46.9% were male. The largest age group (36.4%) was between 26–31 years old, and 61.5% of participants were married. In terms of education, 64.4% held a bachelor’s degree, and 43.1% worked in accounting positions. Most businesses surveyed (84.9%) operated in the service sector, with 44.8% having been in operation for 6–10 years. The majority reported an average monthly income ranging from 50,000,001 to 80,000,001 LAK. The findings indicate that overall user satisfaction with the APTax program for VAT invoice printing was high (????̅ = 4.19, S.D. = 0.41). Respondents most strongly agreed that internet access is essential for effective program use, reflected in the highest average score (????̅ = 4.46, S.D. = 0.61). While the program was generally viewed as user-friendly, the aspect of simplicity received the lowest average rating (????̅ = 3.62, S.D. = 0.79). These results suggest that although overall perceptions are positive, there are areas in need of improvement. Specifically, respondents recommended enhancements such as the ability to define paper size and support for both online and offline functionality.